(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. Cell stresses have a key role on the tumor growth rate, the evolution pattern and on ECM synthesis and organization. In this work, we investigate the interplay between these complex biological phenomena. We develop a heterogeneous tumor growth model subjected to elastic deformation and matrix degradation and remodeling. We incorporate mechanical effects of the surrounding tissue on the growing tumor by assuming that the stress components must satisfy the conservation of linear momentum disregarding inertial effects. We investigate tumor differentiation, morphogenic evolution, and invasion through different feedback mechanism models. Numerical simulations are performed to highlight how mechanical properties of a tissue contribute to cancer progression. Keywords: Mathematical Model, Tumor Growth, Sensitivity Analysis, Mechanical Properties